Teaching of creativity to psychology students at the Universidad Tecnológica de Bolívar (Cartagena, Colombia) (2021)
The following paper presents the pedagogical experience of the psychology program at the Universidad Tecnológica de Bolívar (UTB), a private university in Colombia (Cartagena de Indias) on how this academic program teaches its students the abstract concept of creativity. A fundamental theoretical construct to understand the development of student skills in the artistic field and problem solving, among other factors. The course plans of this academic center are focused on the promotion of a comprehensive training of students and that is why all of them, in addition to the specific subjects of their career, are compulsorily taking subjects from the humanities and other areas. In this way, UTB psychology students acquire knowledge about creativity from three different perspectives: 1. the perspective of cognitive psychology from the subject of Cognition, 2. the vision of the Humanities elective subjects and 3. the economic position from the Creativity and Entrepreneurship course. This multidisciplinary academic curriculum allows the future psychologist to have multiple epistemological approaches to creativity based on different teaching methods